Effect of on‐farm interventions in the aftermath of an outbreak of hypervirulent verocytotoxin‐producing Escherichia coli O157:H7 in Sweden. (5th May 2018) - Tamminen, Lena‐Mari; Fransson, Helena; Tråvén, Madeleine; Aspán, Anna; Alenius, Stefan; Emanuelson, Ulf; Dreimanis, Ilmars; Törnquist, Mats; Eriksson, Erik
Abstract : In 2007, human infections with a hypervirulent strain of verocytotoxin‐producing Escherichia coli O157:H7 increased in Sweden and especially in the Halland County. A connection between the cases and a local beef cattle farm with an on‐farm abattoir and meat processing plant was established. In this observational study the control measures implemented on the infected farm and the dynamics of infection in the herd are described. In May 2008, when measures were initiated and animals put to pasture, the prevalence of positive individuals was 40 per cent and 18 carcasses out of 24 slaughtered animals were contaminated. During summer the monthly prevalence of positive carcasses varied between 8 and 41 per cent and at turning‐in 22 out of 258 individually sampled animals were shedding the pathogen. After January 2009 no positive carcasses were found at slaughter and follow‐up samplings of environment and individuals remained negative until the study period ended in May 2010. The results indicate that on‐farm measures have potential to reduce the prevalence of the pathogen in a long‐term perspective. However, as self‐clearance cannot be excluded the effectiveness of the suggested measures needs to be confirmed.